Athabasca River Avulsion Underway in the Peace-Athabasca Delta, Canada - Wang, Bo; Smith, Laurence C.; Gleason, Colin; Kyzivat, Ethan D.; Fayne, Jessica V.; Harlan, Merritt E.; Langhorst, Theodore; Feng, Dongmei; Eidam, Emily; Munoz, Sebastian; Davis, Julianne; Pavelsky, Tamlin M.; et al. (Alberta Research Council, ARC/AGS Open File Report, 2023)
Avulsions change river courses and transport water and sediment to new channels impacting infrastructure, floodplain evolution, and ecosystems. Abrupt avulsion events (occurring over days to weeks) are potentially catastrophic to society and thus receive more attention than slow avulsions, which develop over decades to centuries and can be challenging to identify. Here, we examine gradual channel changes of the Peace-Athabasca River Delta (PAD), Canada using in situ measurements and 37 years of Landsat satellite imagery. A developing avulsion of the Athabasca River is apparent along the Embarras River–Mamawi Creek (EM) distributary. Its opening and gradual enlargement since 1982 are evident from multiple lines of observation: Between 1984 and 2021 the discharge ratio between the EM and the Athabasca River more than doubled, increasing from 9% to 21%. The EM has widened by +53% since 1984, whereas the Athabasca River channel width has remained stable. The downstream Mamawi Creek delta is growing at a discharge-normalized rate roughly twice that of the Athabasca River delta in surface area. Longitudinal global navigation satellite systems field surveys of water surface elevation reveal the EM possesses a ∼2X slope advantage (8 × 10−5 vs. 4 × 10−5) over the Athabasca River, and unit stream power and bed shear stress suggest enhanced sediment transport and erosional capacity through the evolving flow path. Our findings: (a) indicate that a slow avulsion of the Athabasca River is underway with potentially long-term implications for inundation patterns, ecosystems, and human use of the PAD; and (b) demonstrate an observational approach for identifying other slow avulsions at river bifurcations globally.Plain Language SummaryAvulsions shift river courses and move water and sediment to new channels, which affect infrastructure, floodplains, and ecosystems. Slow avulsions take decades to develop and are more difficult to identify. Using on-the-ground measurements and 37 years of Landsat satellite imagery, we analyze ...